Surgical Application of a Four-Screw Plate for Locking the Physial Section of the Knee Joint in Children Whose Growth Continues - Hertsen, I.H.; Martsyniak, S.M.; Zinchenko , V.V. (TERRA ORTHOPAEDICA, 2024)
Summary. Background. The classic method of surgical treatment of knee joint deformity in the coronal plane is fixation of the epimetaphyseal area using an eight-shaped 2-screw plate according to the concept of guided growth. To improve this technique, we developed, patented and applied a butterfly-like 4-screw quad plate. We also hypothesized that the 4-screw plate would result in faster controlled correction of angular knee deformities than the 2-screw plate. Objective: to improve surgical treatment of children with axial deformity of the knee area, whose growth continues. Materials and Methods. A retrospective analysis of the treatment of 37 children with deformity of the knee in the coronal plane, who were implanted with a 2-screw or 4-screw bone plate, was carried out. The study cohort included both genu varum and genu valgum of both primary and secondary etiology. In dynamics, a comparative analysis of X-ray morphometric parameters obtained from panoramic radiographs of the lower extremities was carried out. Also, depending on the type of implant, the rate of deformity correction and the incidence of complications were compared. Results. We found that the use of a 4-screw plate compared with a 2-screw plate was associated with a shorter interval between implantation and removal, i.e., faster correction. This was confirmed by the indicators of correction of mechanical axis deviation, lateral distal femoral angle and medial proximal tibial angle. No statistically significant difference between the two types of implants was found in the incidence of complications of surgical treatment. Conclusions. Analysis of the rate of correction of clinical and radiomorphometric indicators of deformation of the knee joint in the coronal plane depending on the age periodization of the child’s ontogenesis showed an advantage in the surgical use of a 4-screw quad plate compared to the use of a 2-screw quad plate for fixation of the epimetaphyseal area.